Bioregenera Tion Of Granular Activated Carbon Loaded With Phenol And Ocresol By Immobilized Biomass: Quantification And Kinetic Studies - Toh, Run Hong (2013)
The objectives of this study were to (i) develop a novel approach to bioregenerate GAC loaded with phenol and a-cresol, respectively, using immobilized biomass as well as immobilized PAC-biomass, (ii) quantify and compare the bioregeneration efficiencies of GAC loaded with phenol and a-cresol, respectively using suspended and immobilized biomasses as well as immobilized PAC-biomass, and (iii) develop kinetic models to describe the bioregeneration process of GAC loaded with phenol and a-cresol, respectively, using the immobilized biomass.